Analysis of the Corporate Social Responsibility Program of PT. Balikpapan Wana Lestari for the Community: JEL Classification: M14, L21, Q01, O35, H83 - Muhammad Harianto; Sadly Abdul Djabar; Sri Adrianti Muin (Newinera Publisher, 2026)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR) programs carried out by PT. Balikpapan Wana Lestari (BWL) and their impact on the surrounding community. The research focuses on how the company’s CSR contributes to social, economic, and environmental aspects. A qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings indicate that PT. BWL’s CSR programs include community empowerment, infrastructure development, and environmental initiatives. These programs have provided tangible benefits to community welfare, although challenges remain, such as limited coordination and community participation. The study concludes that CSR implementation at PT. BWL has been conducted effectively but requires strengthening in planning, evaluation, and participation to ensure more sustainable outcomes.